2020
DOI: 10.1111/epi.16632
|View full text |Cite
|
Sign up to set email alerts
|

Postinjury weight rather than cognitive or behavioral impairment predicts development of posttraumatic epilepsy after lateral fluid‐percussion injury in rats

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 46 publications
(120 reference statements)
2
32
0
Order By: Relevance
“…Our hemorrhage-potentiating procedure did not worsen the trauma-induced learning deficits in the MWM and the MAAV tests. In line with prior literature, CCI induced deficits in visuospatial navigation in the MWM [ 43 , 44 , 45 ]. Similarly, both TBI and HTBI groups exhibited deficits in the retention of contextual learning in the MAAV test.…”
Section: Discussionsupporting
confidence: 90%
“…Our hemorrhage-potentiating procedure did not worsen the trauma-induced learning deficits in the MWM and the MAAV tests. In line with prior literature, CCI induced deficits in visuospatial navigation in the MWM [ 43 , 44 , 45 ]. Similarly, both TBI and HTBI groups exhibited deficits in the retention of contextual learning in the MAAV test.…”
Section: Discussionsupporting
confidence: 90%
“…16 Previous studies reported that severe traumatic brain injury induced by lateral fluid-percussion injury to rats caused seizures and SE. 17,18 Co implanted in the motor cortex caused focal seizures. [19][20][21] Co binds to oxygen-binding molecules and causes functional hypoxia, triggers neuronal death, and increases expression of vascular endothelial growth factor.…”
Section: Discussionmentioning
confidence: 99%
“…The cortical tissue damage caused by trauma, hemorrhage, hypoxia, and infection often leads to acute seizures and SE 16 . Previous studies reported that severe traumatic brain injury induced by lateral fluid‐percussion injury to rats caused seizures and SE 17,18 . Co implanted in the motor cortex caused focal seizures 19‐21 .…”
Section: Discussionmentioning
confidence: 99%
“…Impact force, post‐impact apnea time, post‐impact seizure‐like behavior, and body weight were monitored. Occurrence of epileptic seizures was monitored during the sixth post‐injury month by continuous video‐EEG recorded 24 hours/day and 7 days/week as described previously 23–25 . All experiments were approved by the Provincial Government of Southern Finland Animal Ethics Committee and performed in accordance with the guidelines of the European Community Council Directives 2010/63/EU.…”
Section: Methodsmentioning
confidence: 99%